Effects of temperature and light intensity on growth of fodder beet (Beta vulgaris L. var. crassa Mansf.) (Bangladesh Journal of Botany, 2008)
Changes in plant growth viz. leaf area, leaf weight ratio, root weight ratio, dry leaf weight, dry root weight, total plant dry weight, specific leaf area, leaf thickness, leaf area ratio, net assimilation rate and relative growth rate due to the effects of environmental conditions such as temperature and light intensity were described by plant growth models. All equations produced for growth parameters were affected by light intensity and temperature. From multi-regression analysis, close relationships were found between actual and predicted growth parameters. The regression coefficients (r²) of the equations for growth parameters varied from 0.95 to 0.99 for cultivar Ecdogelb and 0.83 to 0.99 for cultivar Ecdorot, respectively.